2001
DOI: 10.1108/eum0000000006289
|View full text |Cite
|
Sign up to set email alerts
|

Organizational cultures, women managers and exclusion

Abstract: Many feminist academics have noted the existence of cultural barriers in their analyses of specific organizations [1]. Other writers have concentrated their efforts on decoding organizational culture for its genderness and have explored different approaches of problematising gendered cultures (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
14

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 22 publications
1
58
0
14
Order By: Relevance
“…As Rutherford (2001) has observed, an organisational culture supporting long working hours tends to have an unintended effect on women in the workplace. Women are less likely and able to comply with those expectations because they do not have as much access to the resource of time as men do.…”
Section: Gender In the 'Field' And Social Contextmentioning
confidence: 99%
“…As Rutherford (2001) has observed, an organisational culture supporting long working hours tends to have an unintended effect on women in the workplace. Women are less likely and able to comply with those expectations because they do not have as much access to the resource of time as men do.…”
Section: Gender In the 'Field' And Social Contextmentioning
confidence: 99%
“…Our results confirm other research that provides evidence that male networks are often an informal field where selection for high level and important board positions takes place. Rutherford (2001) found that limited access to men's networks is the greatest barrier for women in attaining management positions and that women managers are often unaware of these exclusionary practices. Sheridan and Milgate (2003) found that similar criteria were used to recruit men and women members for corporate boards, but that high visibility played a greater role in the selection of women than of men.…”
Section: Toward Recruitment and Selection Processesmentioning
confidence: 99%
“…Although explanations for women's lack of interest in board membership are often framed as reflecting their own preferences and choices, structural and cultural contexts obviously play a significant role and may keep many women out of high-level positions of leadership in sport. Rutherford (2001) argued that women are more likely to want and to attain positions of leadership in organizational cultures that emphasize and create equal opportunities than in organizational cultures where gender differences are denied. The women involved in the current study were also aware of the gendered dynamics of board membership at such a high level and how they had to negotiate stereotypes to be considered a good 'fit.'…”
Section: Strategies Of the Subordinate Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Por esto, la forma en la que están organizados los tiempos laborales ha sido considerada como un freno que bloquea la promoción de las mujeres a puestos de mayor responsabilidad (Rutherford, 2001). Esta forma de entender el compromiso con el trabajo es una de las contradicciones del actual discurso de la igualdad, ya que al mismo tiempo que en la mayoría de las empresas se adoptan políticas de igualdad y conciliación, se mantienen unos horarios que perpetúan la tradicional división de roles.…”
Section: Discusión Y Conclusionesunclassified